Serious Games and Edutainment Applications - Ma, Minhua; Andreas Oikonomo; Lakhmi C. Jain.; SpringerLink (Online service). (London Springer London, 2011)
The recent emergence of serious games as a branch of video games and as a promising frontier of education has introduced the concept of games designed for a serious purpose other than pure entertainment. To date the major applications of serious games include education and training, engineering, medicine and healthcare, military applications, city planning, production, crisis response, to name just a few. If utilised alongside, or combined with conventional training and educational approaches, serious games could provide a more powerful means of knowledge transfer in almost every application domain. Serious Games and Edutainment Applications offers an insightful introduction to the development and applications of games technologies in educational settings. It includes cutting-edge academic research and industry updates that will inform readers of current and future advances in the area. The book is suitable for both researchers and educators who are interested in using games for educational purposes, as well as game professionals requiring a thorough understanding of issues involved in the application of video games technology into educational settings. It is also applicable to programmers, game artists, and management contemplating or involved in the development of serious games for educational or training purposes.
Part I Introduction -- Innovations in Serious Games for Future Learning -- Serious Games: A New Paradigm for Education? -- Origins of Serious Games -- Serious Learning in Serious Games -- Part II Theories and Reviews -- Social Flow and Learning in Digital Games: A Conceptual Model and Research Agenda -- A Formalism to Define, Assess and Evaluate Player Behaviour in Mobile Device Based Serious Games -- Serious Games for Health and Safety Training -- Augmenting Initiative Game Worlds with Mobile Digital Devices -- Part III Custom-Made Games and Case Studies -- Enhancing Learning in Distributed Virtual Worlds through Touch: A Browser-based Architecture for Haptic Interaction -- Operation ARIES!: A Serious Game for Teaching Scientific Inquiry -- From Global Games to Re-contextualized Games: The Design Process of TekMyst -- Using Serious Games for Assessment -- Designing and Evaluating Emotional Student Models for Game-Based Learning -- Fun and Learning: Blending Design and Development Dimensions in Serious Games through Narrative and Characters -- Part IV Use of Commercial-Off-the-Shelf (COTS) Games in Education -- Choosing a Serious Game for the Classroom: An Adoption Model for Educators -- Learning Narratives with Harry Potter. Manuel de Fallass The Prophet Newspaper -- Using Dungeons and Dragons to Integrate Curricula in an Elementary Classroom -- Modding in Serious Games: Teaching Structured Query Language (SQL) Using NeverWinter Nights -- Expanding a VLE-Based Integration Framework Supporting Education in Second Life -- Part V Social Aspects and Gamification -- Casual Social Games as Serious Games: The Psychology of Gamification in Undergraduate Education and Employee Training -- Experiences of Promoting Student Engagement Through Game-Enhanced Learning -- What Computing Students Can Learn by Developing Their Own Serious Games -- Social Interactive Learning in Multiplayer Games -- Index.
Electronic reproduction.
Keywords: Computer games -- Congresses; Educational games -- Congresses; Electronic books